A rAAV2/6 Mutant with Enhanced Targeting for Mouse Retinal Müller Cells. (2nd January 2020) - Cao, Jinjing; Liu, Xiaomei; Yuan, Yun; Wang, Feifei; Kong, Wen; Shi, Guohua; Li, Wensheng; Zhang, Chun
ABSTRACT: Purpose: Adeno-associated virus vector (AAV) is the most accepted gene delivery vector for retinal gene therapy. Müller cells play an important role in maintaining homeostasis and neuronal structural integrity, stability and it has been found to be involved in many retinopathies. The aim of this study is to identify a rAAV2/6 mutant which has increased tropism for Müller cell of the mouse retina. Materials and Methods: Using amino acid mutagenesis, we created a rAAV2/6 capsid mutant, rAAV2/6-S663L. In vivo imaging and retinal flat mount were employed to analyze the gene expression of rAAV2/6-S663L and wt rAAV2/6 in mouse retinal tissue. Retinal tissue cryosection, immunohistochemistry (IHC), Müller cell-specific promoter-controlled gene expression, and double AAV fluorescent protein co-expression were performed to determine the targeting of rAAV2/6-S663L for mouse retinal Müller cells. Results: In vivo imaging, retinal flat mount and retinal tissue cryosection results showed that rAAV2/6-S663L and wt rAAV2/6 have different specific tropisms in mouse retina and rAAV2/6-S663L is more preferentially targeting Müller cells. Müller cell-specific promoter-controlled gene expression experiments and IHC test confirmed that rAAV2/6-S663L has a higher tendency to infect Müller cells than wt rAAV2/6. Co-infection of the mouse retina with one rAAV2/6-S663L expressing EGFP under the control of GFAP promoter and the other one expressing mCherry under the control of CMV promoter revealed co-expression of the two fluorescent proteins in Müller cells. Conclusions: The results confirmed that rAAV2/6-S663L has a higher tropism for Müller cells than wt rAAV2/6. Our findings could add a new useful tool for retinal disease gene therapy.